2008
DOI: 10.3749/canmin.46.2.379
|View full text |Cite
|
Sign up to set email alerts
|

THE Ta-Nb-Sn-Ti OXIDE-MINERAL PARAGENESIS FROM LA VIQUITA, A SPODUMENE-BEARING RARE-ELEMENT GRANITIC PEGMATITE, SAN LUIS, ARGENTINA

Abstract: The paragenesis and chemical composition of the primary Ta-Nb-Sn-Ti oxide minerals in the La Viquita spodumene-bearing granitic pegmatite, San Luis, Sierras Pampeanas, Argentina, evolved from the border zone inward. Early phases consist of minor columbite-(Fe) in the border and wall zones. In the intermediate zones, formed by a coarse-grained association of Kfs + Qtz + Ms + Ab with inwardly increasing proportions of spodumene, homogeneous or oscillatory-zoned columbite-(Fe) crystals occur in the outer parts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…These textures have been cited in many other occurrences (e.g. Galliski et al, 2008;Wise and Brown, 2010;Zhu et al, 2015)…”
Section: Overprints On Cgmmentioning
confidence: 89%
See 1 more Smart Citation
“…These textures have been cited in many other occurrences (e.g. Galliski et al, 2008;Wise and Brown, 2010;Zhu et al, 2015)…”
Section: Overprints On Cgmmentioning
confidence: 89%
“…These textures have been cited in many other occurrences (e.g. Galliski et al ., 2008; Wise and Brown, 2010; Zhu et al ., 2015), are known as ‘sponge-like’ textures and resemble textures related to overprinting processes in an environment enriched in fluids during their formation. However, the origin of this fluid is an open issue but could be linked to the evolution of the magma itself or to processes unrelated to the magmatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Beurlen et al (2006) reported an occurrence of cassiterite lamellae arranged in three directions in ilmenite, resulting possibly from a decomposition of a hypothtical "Sn-rich ilmenite" precursor. Cassiterite hosted by columbite is also cited in two granitic pegmatites, although this phenomenon is not clearly interpreted as an exsolution product or a simple intergrowth (Černý et al 2004;Galliski and Marquez-Zavalía 2008). Cassiterite is isostructural with rutile, but it is very rarely present as inclusions in rutile.…”
Section: Introductionmentioning
confidence: 93%
“…In this sense, pegmatites, as one type of these granitic systems, are of great interest and represent an important target for the mining of columbite-tantalite (CT) group minerals and other strategic elements (e.g., [1,[4][5][6]). The chemistry of Nb-Ta-Sn oxides, as well as quartz, feldspars, and micas, 2 of 26 among others, is frequently used to reveal local trends within individual pegmatite bodies and regional magma fractionation trends across pegmatite fields (e.g., [7][8][9][10][11][12][13][14]). In Nb-Ta oxides, the increase in the Ta/(Ta+Nb) and/or Mn/(Mn+Fe) ratios (X Ta and X Mn , respectively), for example, indicates increasing fractionation degrees of the pegmatite melt (e.g., [15][16][17]).…”
Section: Introductionmentioning
confidence: 99%